Assessing the Motives and Gratification of Virtual Community - Widayat Widayat (Journal of Innovation in Business and Economics, 2019)
The objective of this study was to identify the pillars of the existence of virtual community groups through the motive and gratification theory approach. The data were collected using Google form and being sampled with a nonprobability technique. The data were analyzed using factor analysis employing Jeffrey’s Amazing Statistics Program (JASP) software. The result showed that the satisfaction obtained encourages the fulfillment of social obligations and respect. The act of giving one another, fostering a sense of philanthropy, spreading useful information to meet the needs of the basic non-physical, then move to meet the higher requirements, social, religious motivation and reaching higher needs, to worship and get the reward from God. The literature also reveals that virtual groups can meet specific work needs on aspects of effectiveness and efficiency.